PERAN GURU DALAM PEMBELAJARAN BERDIFERENSIASI PADA PELAJARAN SBDP DI SD NEGERI 1 TANJUNG - Adhi Prasetiyo Nogroho; Lia Mareza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the role of teachers in differentiated learning in SBdP subjects for inclusive students and to describe the supporting and inhibiting factors of the teacher's role in differentiated learning for inclusive students. This research uses qualitative case study research. Data collection techniques use observation, interviews and documentation. The results of this research show that the teacher's role in differentiated learning in SBdP lessons at SD Negeri 1 Tanjung has a positive impact on regular and inclusive students. The role of the teacher at SD Negeri 1 Tanjung class VB in the SBdP lesson is that there is a teacher's role as a facilitator, as an evaluator and as an inspirer. Of course, from the role of the teacher mentioned above, the teacher's role already exists in it, there is a teacher's role in accordance with differentiated learning in the Merdeka curriculum, which has 4 learning components, namely content, process, product and learning environment.